YIELD COMPONENT PERFORMANCE AND PRODUCTIVITY OF RICE INPARI 13 VARIETIES IN VARIOUS PLANTING SYSTEM - Yuti Giamerti; Zuraida Yursak (Widyariset, 2013)
The purpose of this research is to know yield components performance and productivity of Inpari 13 varieties’s rice in planting systems of jajar legowo 2:1, legowo 4:1 and tegel. The rice was planted at 3 hectares of farmers’rainfed area in Mauk regency of Tangerang district. This location was a demfarm of SLPTT Banten Assesment Institute for Agricultural Technology. This research was held from April to August 2011. Planting system of jajar legowo 2:1, Legowo 4:1 and tegel compared yield components variable and of Inpari 13 varieties’s rice. The results showed that Inpari 13 varieties’s rice growed more optimal and had high productivity with planting systems of legowo 2:1(6,57 ton/ha) then legowo 4:1 (5,57 ton/ha) and tegel (5,09 ton/ha).